2013
DOI: 10.1063/1.4827019
|View full text |Cite
|
Sign up to set email alerts
|

Challenges and opportunities for multi-functional oxide thin films for voltage tunable radio frequency/microwave components

Abstract: There has been significant progress on the fundamental science and technological applications of complex oxides and multiferroics. Among complex oxide thin films, barium strontium titanate (BST) has become the material of choice for room-temperature-based voltage-tunable dielectric thin films, due to its large dielectric tunability and low microwave loss at room temperature. BST thin film varactor technology based reconfigurable radio frequency (RF)/microwave components have been demonstrated with the potentia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
75
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 147 publications
(75 citation statements)
references
References 207 publications
(254 reference statements)
0
75
0
Order By: Relevance
“…Many ME systems based on ferromagnetic/ferroelectric heterostructures have been developed, encompassing voltage-tunable microwave signal processing devices [3][4][5], magnetoelectric random access memory devices [6][7][8][9] and strain-control GMR devices [10][11][12]. For all these kinds of systems, the properties are controlled via the elastic voltage-induced strains transmitted from the ferroelectric medium to the ferromagnetic one.…”
Section: Introductionmentioning
confidence: 99%
“…Many ME systems based on ferromagnetic/ferroelectric heterostructures have been developed, encompassing voltage-tunable microwave signal processing devices [3][4][5], magnetoelectric random access memory devices [6][7][8][9] and strain-control GMR devices [10][11][12]. For all these kinds of systems, the properties are controlled via the elastic voltage-induced strains transmitted from the ferroelectric medium to the ferromagnetic one.…”
Section: Introductionmentioning
confidence: 99%
“…It is obvious that, whether isolated or not, OVs result in the increase of dielectric loss. To avoid such an unfavorable effect and save energy, a smart strategy is to treat a ferroelectric device with high-pressure oxygen annealing [10,11]. In this protocol, the OV sites can be occupied by oxygen and thus the dielectric loss is reduced [10].…”
Section: Discussionmentioning
confidence: 99%
“…Moreover this structure may be tuned by strain [8,9]. It has also been confirmed that dielectric loss increases with the increase of the OV concentration [10,11]. To the best of our knowledge, however, micromechanism of OV behind the exceptional dielectric loss remains largely unexplored due to lack of an effective protocol for experiments.…”
Section: Introductionmentioning
confidence: 99%
“…Role of film stoichiometry and interface quality in the performance of (Ba,Sr)TiO 3 Parallel plate capacitors with quality factors exceeding 1000 were fabricated using Ba 0.3 Sr 0.7 TiO 3 (BST) thin films grown by hybrid molecular beam epitaxy on epitaxial Pt bottom electrodes. The influence of film stoichiometry was investigated by varying the (Ba þ Sr)/Ti ratio around the stoichiometric composition.…”
mentioning
confidence: 99%
“…[1][2][3][4][5] A main focus of materials and device optimization is to simultaneously achieve high quality factors (Q ¼ 1/tand, where tand represents the dielectric loss tangent) while tuning the capacitance at least by a factor of two with an applied DC bias. 2,6 Q-factors exceeding 1000 and tunabilities up to 5:1 were reported in BST films that were grown by molecular beam epitaxy (MBE).…”
mentioning
confidence: 99%